2020
DOI: 10.21203/rs.3.rs-20710/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The circulating levels of CTRP5 and the ratio of CTRP1 to CTRP5 plasma levels are significant predictors for cIMT value in patients with type 2 diabetes

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…CTRP1 and CTRP1/CTRP5 ratio were markedly higher in male AS patients with T2DM compared to controls, indicating that these CTRPs might have a causal role for cardio-metabolic risk in T2DM. In addition, the ratio of CTRP1 to CTRP5 in plasma is positively correlated with carotid intima-media thickness in the whole population (14). Lei, X. et al found the positive association between elevated expression of CTRP2 and BMI in obesity (16).…”
Section: Pro-atherosclerotic Markersmentioning
confidence: 98%
“…CTRP1 and CTRP1/CTRP5 ratio were markedly higher in male AS patients with T2DM compared to controls, indicating that these CTRPs might have a causal role for cardio-metabolic risk in T2DM. In addition, the ratio of CTRP1 to CTRP5 in plasma is positively correlated with carotid intima-media thickness in the whole population (14). Lei, X. et al found the positive association between elevated expression of CTRP2 and BMI in obesity (16).…”
Section: Pro-atherosclerotic Markersmentioning
confidence: 98%